Smart cities: Between worlding and provincialising. (February 2021) - Burns, Ryan; Fast, Victoria; Levenda, Anthony; Miller, Byron
We introduce key concepts that have guided the diverse case studies of this special issue on smart cities. Calling into question Global North conceptions of the smart city, nine different articles analyse smart city projects around the world, with particular attention paid to the need to provincialise our understanding of these projects as well as to consider their relationship to worlding strategies. These case studies demonstrate the diversity of what smart cities can be and the need to consider, through comparative analysis, the broader power geometries in which they are imbedded.